Neurotoxicity mechanisms and clinical implications of six common recreational drugs - Wang, Jing; Hao, Yulei; Ma, Di; Feng, Liangshu; Yang, Feng; An, Pingxu; Su, Xingqi; Feng, Jiachun (Frontiers in Pharmacology, 2025)
The recreational abuse of addictive drugs poses considerable challenges to public health, leading to widespread neurotoxicity and neurological dysfunction. This review comprehensively examines the neurotoxic mechanisms, clinical manifestations, and treatment strategies associated with six commonly abused substances: methamphetamine, cocaine, synthetic cathinones, ketamine, nitrous oxide and heroin. Despite their diverse pharmacological properties, these drugs converge on shared neurotoxic pathways, including oxidative stress, mitochondrial dysfunction, excitotoxicity, and neuroinflammation. Psychostimulants, such as methamphetamine, cocaine and synthetic cathinones, disrupt monoaminergic neurotransmission, causing cognitive impairment, psychiatric disturbances, and neurovascular damage. Dissociative anesthetics, including ketamine and nitrous oxide, impair glutamatergic transmission and mitochondrial function, thereby exacerbating excitotoxicity and neuronal apoptosis. Opioids, such as heroin, primarily target the brain’s reward system and induce oxidative stress, neuroinflammation, and cerebrovascular complications. Treatment strategies remain limited, focusing on symptomatic management, neuroprotective interventions, and behavioral therapies. Emerging approaches, such as antioxidants, NMDA receptor modulators, and cognitive rehabilitation, show promise but require further validation. By highlighting the underlying mechanisms and therapeutic challenges, this review provides a foundation for developing targeted interventions and advancing research on drug-induced neurotoxicity.